2021
DOI: 10.1101/2021.03.05.21252848
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19-associated school closures and related efforts to sustain education and subsidized meal programs, United States, February 18–June 30, 2020

Abstract: Pre-emptive school closures are frontline community mitigation measures recommended by CDC for implementation during severe pandemics. This study describes the spatiotemporal patterns of publicly announced school closures implemented in response to the coronavirus disease 2019 (COVID-19) pandemic and assesses how public K-12 districts adjusted their methods of education delivery and provision of subsidized meals. During February 18–June 30, 2020, we used daily systematic media searches to identify publicly ann… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…2 , 3 , 4 , 5 , 6 Indeed, in the first four months of the pandemic (March to June 2020), therapy service disruption was reported worldwide.5,7–14 These disruptions included services provided through public schools, 15 asschools in 48 US statesclosed in the US from March to June of 2020 . 13 The range of disruptions included a total lack of access to services, 11 a decrease in services, 5 , 8 , 9 , 10 , 14 a switch to a telehealth model of service provision, 16 , 17 and the need for parents to take over as primary therapy providers. 7 In addition to the substantial impact on parental and caregiver mental health 18 , 19 , 20 , 21 , the lack of (or decreased) access to therapy services negatively affected the physical and mental health7,9,20,22–26 and behavior 21 , 22 , 23 of children with disabilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 , 3 , 4 , 5 , 6 Indeed, in the first four months of the pandemic (March to June 2020), therapy service disruption was reported worldwide.5,7–14 These disruptions included services provided through public schools, 15 asschools in 48 US statesclosed in the US from March to June of 2020 . 13 The range of disruptions included a total lack of access to services, 11 a decrease in services, 5 , 8 , 9 , 10 , 14 a switch to a telehealth model of service provision, 16 , 17 and the need for parents to take over as primary therapy providers. 7 In addition to the substantial impact on parental and caregiver mental health 18 , 19 , 20 , 21 , the lack of (or decreased) access to therapy services negatively affected the physical and mental health7,9,20,22–26 and behavior 21 , 22 , 23 of children with disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…In the 18 months since its onset, the impact of therapy disruptions on children with disabilities during the pandemic’s early months have been well-documented. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 Yet the potential links between individual or environmental factors and access to services between March and July of 2020 remain unexplored. Many individual and environmental factors may have influenced access to therapy during the pandemic’s early months, including age, disability severity, therapeutic goals, availability of technological devices, 29 and whether therapy services were previously received through school or outside of school.…”
Section: Introductionmentioning
confidence: 99%
“…Given the results of this study which documented that prolonged school closures occur annually even outside of a global pandemic, and given the experience of the still-ongoing COVID-19 pandemic [22], it appears that there is already a solid investment case for creating sustainable solutions for high quality digital learning and innovative supplemental feeding programs nationwide before next disaster strikes, with particular attention and urgency for disaster-prone areas and socio-economically vulnerable communities.…”
Section: Discussionmentioning
confidence: 90%
“…In summary, our study demonstrated that while only 2% of all unplanned school closures during the 8year study period were categorized as prolonged, (lasting ≥5 days), such closures occur annually due to a variety of causes and have major impacts on schools, students, teachers, and families. The establishment of a publicly available reporting system for school closures at the state or national level could lead to a better understanding of the magnitude and duration of PUSCs, both during the inter-pandemic period like the one on which we reported here (2011-2019) and during the major public health emergencies like severe influenza outbreaks [17] or during the respiratory infectious disease pandemics [6,22,31]. Further studies are needed to elucidate the economic and social consequences of PUSCs, both those occurring outside of a pandemic and those which are pandemic-related, particularly for those populations that are disproportionately affected, and inform preparedness guidelines for future occurrences of prolonged unplanned school closures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation